2007
DOI: 10.1001/archinte.167.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Chronic Obstructive Pulmonary Disease

Abstract: Background: Depressive symptoms are common among patients with chronic obstructive pulmonary disease (COPD), but depression's impact on COPD outcomes has not been fully investigated. We evaluated the impact of comorbid depression on mortality, hospital readmission, smoking behavior, respiratory symptom burden, and physical and social functioning in patients with COPD. Methods: In this prospective cohort study, 376 consecutive patients with COPD hospitalized for acute exacerbation were followed up for 1 year. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
198
5
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 550 publications
(235 citation statements)
references
References 37 publications
12
198
5
6
Order By: Relevance
“…We found that psychological disorders such as depression and anxiety in subjects with COPD were significantly associated with all subscales of the SGRQ according to the simple correlation, but only anxiety disorders were independently associated with SGRQ total scores in linear regression analysis. Ng et al 25 reported that depressed subjects with COPD had significantly worse HRQOL in all subscales of the SGRQ. Andenaes et al 26 reported a significant relationship between depression scores and the respiratory-specific SGRQ impact subscale in subjects with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…We found that psychological disorders such as depression and anxiety in subjects with COPD were significantly associated with all subscales of the SGRQ according to the simple correlation, but only anxiety disorders were independently associated with SGRQ total scores in linear regression analysis. Ng et al 25 reported that depressed subjects with COPD had significantly worse HRQOL in all subscales of the SGRQ. Andenaes et al 26 reported a significant relationship between depression scores and the respiratory-specific SGRQ impact subscale in subjects with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality and readmission rate among anxious and/or depressive COPD patients increases during the 30 days following hospitalisation [68]. The presence of depression has prognostic value, as shown in a study in COPD patients hospitalised for exacerbation [69]. Mortality following a COPD exacerbation was greater among the depressive patients.…”
Section: Anxiety and Depression Disordersmentioning
confidence: 96%
“…Indeed, anxiety was found to be related to increased risk of relapse after exacerbation [208] and hospital readmission [209]. The role of depression on exacerbation is less clear but it has prognostic value because it extends the duration of hospitalisation [69,210]. In the same way, metabolic syndrome has an impact in exacerbation.…”
Section: Copd Comorbidities Impact On Exacerbationsmentioning
confidence: 99%
“…The first was conducted by Light evaluating the association between physical factors and depression in 1985 13 .Until 2007, most studies denied an association between depression and physical measurements of COPD. In contrast, most studies since 2008 have affirmed a positive association between depression and physical measurements of COPD.…”
Section: Discussionmentioning
confidence: 99%